2018
DOI: 10.1002/acn3.555
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive and functional connectivity alterations in Friedreich's ataxia

Abstract: ObjectiveThe aim of this study was to perform the first resting‐state functional MRI (RS‐fMRI) analysis in Friedreich's ataxia (FRDA) patients to assess possible brain functional connectivity (FC) differences in these patients, and test their correlations with neuropsychological performances.MethodsIn total, 24 FRDA patients (M/F: 15/9, mean age 31.3 ± 15.0) and 24 healthy controls (HC; M/F: 15/9, mean age 30.7 ± 15.5) were enrolled in this cross‐sectional study. All patients underwent a thorough neuropsycholo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(36 citation statements)
references
References 41 publications
3
33
0
Order By: Relevance
“…Therefore, the cognitive deficit reported in FDRA may be the consequences of these abnormalities in the cerebellar-cortical system (e.g. Cocozza et al, 2018;Selvadurai et al, 2020;Zalesky et al, 2014). In this same line, the cognitive changes observed in this research may be related to the longitudinal microstructural changes reported in diffusion tensor imaging studies (Mascalchi et al, 2016;Rezende et al, 2016).…”
Section: Discussionsupporting
confidence: 52%
“…Therefore, the cognitive deficit reported in FDRA may be the consequences of these abnormalities in the cerebellar-cortical system (e.g. Cocozza et al, 2018;Selvadurai et al, 2020;Zalesky et al, 2014). In this same line, the cognitive changes observed in this research may be related to the longitudinal microstructural changes reported in diffusion tensor imaging studies (Mascalchi et al, 2016;Rezende et al, 2016).…”
Section: Discussionsupporting
confidence: 52%
“…On the microstructural level, changes in fractional anisotropy by diffusion MRI are consistently detected in the deep cerebellar white matter and in the dentatothalamic tracts, 39,40,[47][48][49][50] which appear to correlate with ataxia severity. Correspondingly, several studies detected impaired cerebellocerebral connectivity, 17,[51][52][53] which is essentially due to atrophy of dentatothalamic fibers. Overall, imaging confirms the presence and progression of cerebellar pathology in FRDA, mostly, but not exclusively, affecting the DN, and the consequent impairment in structural and functional connectivity.…”
Section: Cerebellar Systemmentioning
confidence: 99%
“…Previous neuroimaging investigations suggested that the level of rsFC is linked with FRDA patients' neurological status. A resting‐state functional magnetic resonance imaging (rfMRI) study described that a higher level of rsFC between superior and medial frontal gyri, and angular and cingulate‐paracingulate gyri might be associated with better cognitive performances in FRDA patients (Cocozza et al, 2018). Furthermore, a previous magnetoencephalography (MEG) study from our group showed that FRDA patients with symptoms onset after age 12 had significantly higher levels of brain rsFC compared with matched healthy individuals and FRDA patients with symptoms onset before age 12 (Naeije et al, 2020b).…”
Section: Introductionmentioning
confidence: 99%